JUDICIAL DEPOSITION OF TESTIMONY ACCORDING TO THE NEW CRIMINAL PROCEDURE CODE OF THE REPUBLIC OF ARMENIA - Melkonyan, Davit (State and Law, 2021)
The article is dedicated to one of the innovations of the new Criminal Procedure Code of the Republic of Armenia - the institute of judicial deposition of testimony. The author states that the model of judicial deposition of testimony enshrined in the new Code is in fact aimed at two main purposes: to ensure the real possibility of exercising the right of the accused to cross-examine; on the other hand, to significantly expand the defense opportunities. In contrast to the current rules, according to which the collection of evidence during pre-trial proceedings is a monopoly of the prosecution, the model of deposition of testimony essentially allows a defense attorney not only to obtain evidence, but also to have this evidence already secured during pre-trial proceedings, which greatly complicates the possibility of challenging the legality acquisition procedures. Recognizing that this institution is new for the domestic litigation and that unforeseen problems may arise during its practical operation, the author notes that the broad system of legal guarantees is designed to neutralize potential problems as much as possible.
Keywords: deposition of testimony; court; accused; absent witness; cross-examination